JURIDICAL REVIEW NON-PENAL MEANS AS IN PREVENTION LEGAL PROTECTION OF PERSONAL DATA ACCORDING TO APPLICABLE PROVISION - Mangihut Mangihut; Nursyamsuddin Nursyamsuddin (Sean Institute, 2023)
The development of information and communication technology that hit the world is a new wave that significantly changes human life. Technology is part of the driving force that actively influences world human civilisation by offering various benefits and conveniences. In this era, almost all levels of society have enjoyed the benefits of technology, from the lower layers to the highest levels of society. Likewise, the government, trade/business, education and so on are not spared. The magnitude of the benefits provided by this technology has a large risk impact. Technology is used for things that are not good. Most communication and information technologies that are developing in the modern era, like today will only be accessible or utilized if the user already has a personal account obtained by registering or registering. To register, of course, by entering a number of personal data stored in a data repository by the service provider. So, this user data handed over to the service provider is a gap or an opening for a problem. Leakage of personal data owned by users seems unavoidable if the service provider's security system could be more optimal. Incidents of personal data leaking have occurred a lot and almost happened in various sectors. Many factors cause data leaks, including weak security systems from service providers, lack of user awareness to maintain the security of their data, and cyber criminals who use other people's data for personal interests and benefits. This paper will provide an overview of the legal provisions of non-penal means in the protection of personal data, how are the procedures for prevention through non-penal means in the protection of personal data law, as well as the factors that influence prevention through non-penal means in the protection of personal data law.